2020
DOI: 10.1039/c9en01302d
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene mediates CuO NP-induced ultrastructural changes and oxidative stress inArabidopsis thalianaleaves

Abstract: Metallic oxide nanoparticles (NPs) have received great importance due to their unique properties and valuable applications in various fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Moreover, studies have shown that Arabidopsis roots, leaves, flowers and harvested seeds treated with CuO NPs contained significantly higher Cu elements than CuO bulk particles (BPs) and Cu 2+ treatment, demonstrating that CuO BPs cannot be readily accumulated and distributed in the plant (Figure 8), indicating that CuO NPs themselves have high mobility in Arabidopsis. In combined ethylene experiments, CuO NPs were observed to induce oxidative stress and inhibit growth by affecting the rosette size, biomass, chlorophyll content, lipid peroxidation, accumulation of oxygen species and cellular ultrastructure of Arabidopsis [38,68]. Interestingly, Jia et al found that the Cys cycle affected the uptake and intracellular transport of CuO NPs.…”
Section: Toxic Effects At the Physiological Levelmentioning
confidence: 99%
“…Moreover, studies have shown that Arabidopsis roots, leaves, flowers and harvested seeds treated with CuO NPs contained significantly higher Cu elements than CuO bulk particles (BPs) and Cu 2+ treatment, demonstrating that CuO BPs cannot be readily accumulated and distributed in the plant (Figure 8), indicating that CuO NPs themselves have high mobility in Arabidopsis. In combined ethylene experiments, CuO NPs were observed to induce oxidative stress and inhibit growth by affecting the rosette size, biomass, chlorophyll content, lipid peroxidation, accumulation of oxygen species and cellular ultrastructure of Arabidopsis [38,68]. Interestingly, Jia et al found that the Cys cycle affected the uptake and intracellular transport of CuO NPs.…”
Section: Toxic Effects At the Physiological Levelmentioning
confidence: 99%
“…On the other hand, no significant effects on shoot fresh biomass were observed by treating with CeO 2 NPs to rice at 200 mg L –1 , while the root fresh weight was significantly inhibited . Azhar et al and Wang et al reported that CuO NPs at 50 mg L –1 had no significant effects on Arabidopsis leave growth. , However, the fresh or dry biomass was significantly reduced with the increased CuO NPs concentrations ranging from 100 to 400 mg L –1 . The element of Ti was also not essential to plants, whereas some literatures indicated that TiO 2 NPs could promote the growth of plants .…”
Section: Introductionmentioning
confidence: 99%
“…34 that CuO NPs at 50 mg L −1 had no significant effects on Arabidopsis leave growth. 35,36 However, the fresh or dry biomass was significantly reduced with the increased CuO NPs concentrations ranging from 100 to 400 mg L −1 . 35 The element of Ti was also not essential to plants, whereas some literatures indicated that TiO 2 NPs could promote the growth of plants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a yet recent study, the results of Azhar et al advocated that nCuO adversely affected the Arabidopsis biomass, chlorophyll contents, guard cells, stomatal pore, and various cell organelles, with a consequent increase in the ROS accumulation in all four Arabidopsis genotypes studied. These reports suggested that various NPs had negative impacts on different crop plants [23].…”
Section: Introductionmentioning
confidence: 99%